Improving the Quality of ST Yowana Mekar’s Youth Organization Through Culturally Based Articles of Association – Bylaws - I Wayan Kartika Jaya Utama; I Wayan Werasmana Sancaya; I Made Aditya Mantara Putra; IB Gede Agustya Mahaputra; Ketut Adi Wirawan (Fakultas Hukum, Universitas Warmadewa, 2023)
This community service program aims to provide training and assistance in making the Articles of Association Document of the Bylaws and Organizational Administration Tools for the youth management of ST Yowana Mekar, which is assisted by lecturer service. Through this activity, it is hoped that the youth management of ST Yowana Mekar can organize their organization in a healthy, orderly, and orderly manner so that the Vision can be realized. The method used to achieve the goal is technical and participatory guidance. The form of participatory empowerment activities is in the form of active participation of participants in activities carried out by the team in workshops, mentoring, and monitoring-evaluation. The steps of its activities are as follows: 1) Workshop on the Articles of Association document of the Bylaws for an organization, to provide an understanding of the importance of the Articles of Association document of the Bylaws for an organization, 2) Training on making documents of the Articles of Association of the Bylaws, 3) Assistance in finalizing the preparation of the Articles of Association document of the Bylaws. The result of the activity is: that the Youth organization ST Yowana Mekar can create and have a Balinese-language Bylaws document of the Bylaws.